Simulasi Pompa Pada Kolam Retensi Untuk Penanganan Banjir Pada Drainase Jalan Belimbing Kota Dumai - Handayani, Yohanna Lilis; Simanjuntak, Valentino; Siswanto, Siswanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Drainage system with retention pond and pump is the effective and effisien way for handling flood that happens. This study tries to keep the system for handling the flood at Belimbing Street of Dumai City. This study conducted a simulation retention pond and pump capacity by using water balance method. Retention pond and pump drainage system are designed using 10 year return period flood discharge. The discharge had been calculated by Rational method and IDF curve by Mononobe method. Reservoir pond need to be sized 5600 m3 (70m x 40m x 2m) and using effisien pumping capacity of 0,5 m3 / sec to handle the floodwater at Belimbing Street of Dumai City.Keywords: flood, drainage system, retention pond, pump